Somatostatin interneuron fate-mapping and structure in a Pten knockout model of epilepsy - Drake, Austin W.; Jerow, Lilian G.; Ruksenas, Justin V.; McCoy, Carlie; Danzer, Steve C. (Frontiers in Cellular Neuroscience, 2024)
Disruption of inhibitory interneurons is common in the epileptic brain and is hypothesized to play a pivotal role in epileptogenesis. Abrupt disruption and loss of interneurons is well-characterized in status epilepticus models of epilepsy, however, status epilepticus is a relatively rare cause of epilepsy in humans. How interneuron disruption evolves in other forms of epilepsy is less clear. Here, we explored how somatostatin (SST) interneuron disruption evolves in quadruple transgenic Gli1-CreERT2, Ptenfl/fl, SST-FlpO, frt-eGFP mice. In these animals, epilepsy develops following deletion of the mTOR negative regulator Pten from a subset of dentate granule cells, while downstream Pten-expressing SST neurons are fate-mapped with GFP. The model captures the genetic complexity of human mTORopathies, in which mutations can be restricted to excitatory neuron lineages, implying that interneuron involvement is later developing and secondary. In DGC-Pten KOs, the density of fate-mapped SST neurons was reduced in the hippocampus, but their molecular phenotype was unchanged, with similar percentages of GFP+ cells immunoreactive for SST and parvalbumin (PV). Surviving SST neurons in the dentate gyrus had larger somas, and the density of GFP+ processes in the dentate molecular layer was unchanged despite SST cell loss and expansion of the molecular layer, implying compensatory sprouting of surviving cells. The density of Znt3-immunolabeled puncta, a marker of granule cell presynaptic terminals, apposed to GFP+ processes in the hilus was increased, suggesting enhanced granule cell input to SST neurons. Finally, the percentage of GFP+ cells that were FosB positive was significantly increased, implying that surviving SST neurons are more active. Together, findings suggest that somatostatin-expressing interneurons exhibit a combination of pathological (cell loss) and adaptive (growth) responses to hyperexcitability and seizures driven by upstream Pten KO excitatory granule cells.